Visibly restricted: public opinion and the representation of immigrant origin communities across Great Britain. Issue 9 (4th July 2019) - English, Patrick
ABSTRACT: This research brings together literatures on public opinion and political representation into a political opportunity framework to investigate the impact that changing public opinion toward immigration has on the parliamentary descriptive representation of immigrant groups in Great Britain. It breaks down Britain's immigrant groups into white and non-white (ethnic minority) backgrounds, so as to investigate the specific barriers posed by both immigrant status and minority ethnic status. Using new data on the backgrounds of nearly 1, 500 MPs over the past five parliaments, and Stimson dyadic-ratios aggregations of 1, 000 survey marginals on immigration from five high-quality sources, this research concludes that increasingly negative public opinion does indeed restrict the descriptive representation of ethnic minority immigrant origin groups in Britain, but not white immigrant origin groups. Preliminary analysis of candidate data suggests that parties place minority candidates in "unwinnable" seats in areas of high anti-immigrant public opinion.